Corpus of Contemporary Czech Poetry: A database for research on contemporary poetic language across media. - Škrabal, Michal; Piorecký, Karel (Digital Scholarship in the Humanities, 2022)
Our article reports on the emerging Corpus of Contemporary Czech Poetry and the possibilities for its use. We describe the genesis of the idea of creating a specific corpus that combines the principles of synchronicity and genre instead of relying on the presence of poetry in the general corpus of contemporary Czech. We also characterize the structure of our corpus, which is designed to cover both of the basic media areas in which contemporary poetry is published and distributed: either in books or through open publishing platforms on the Internet (literary forums). We additionally describe the functionalities of the tools for mining the corpus data, which are designed to easily serve comparative analyses across media (print/web). We suggest how useful quantitative data analysis can be in the first phase of language-oriented literary research; or rather we point out the necessity of combining quantitative and qualitative approaches. Only the researcher's interpretative proficiency can decide on the boundaries of the field under study and the meaning of the elements present in it. In text-centred analyses, language corpora should start to play a similar role as other tools of scientific infrastructure, such as bibliographic databases.